PELATIHAN PEMBUATAN WORKSHEET INTERAKTIF DENGAN WIZER.ME UNTUK MENGOPTIMALKAN PEMBELAJARAN DI SD NEGERI 26 MATARAM - Muhammad Sobri; Dyah Indraswati; Aisa Nikmah Rahmatih; Asri Fauzi; Lalu Wira Zain Amrullah (Jurnal Warta Desa (JWD), 2022)
As an effort to improve teacher competence in developing interactive and interesting learning resources, training on making interactive worksheets was carried out with wizer.me. Wizer.me has full features for making online assignments. In terms of appearance, this platform is dynamic but simple. There are several features provided by wizer.me including community, worksheets, create new worksheets, learners, and coffee room. This community service activity is divided into three stages, namely the preparation stage, the implementation stage, and the evaluation stage. This service is targeted at the teachers of SDN 26 Mataram, totaling 14 people. The training was conducive because 14 participants were guided by 5 members of the service team so that if there were difficulties, they could be resolved immediately. Participants were also enthusiastic about participating in the training because the presenters presented in a communicative language and guided step by step while making sure the participants had gone through each step well. The Service Team has also prepared emails that can be used as well as questions so that participants only need to input them. Some participants were also active in asking if there was something they didn't understand. Given the limited time, there are only 5 types of questions that can be practiced by participants, including multiple-choice, blank, matching, fill-on image, and word search puzzles.